2020
DOI: 10.1177/0333102420949202
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and aura triggered by normobaric hypoxia

Abstract: Background For future experimental studies or the development of targeted pharmaceutical agents, a deeper insight into the pathophysiology of migraine is of utmost interest. Reliable methods to trigger migraine attacks including aura are desirable to study this complex disease in vivo. Methods To investigate hypoxia as a trigger for migraine and aura, we exposed volunteers diagnosed with migraine, with (n = 16) and without aura (n = 14), to hypoxia utilizing a hypoxic chamber adjusted to a FiO2 of 12.6%. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
0
17
0
2
Order By: Relevance
“…It has been shown that exposure of migraine subjects to normobaric hypoxia can trigger both the migraine attacks and the manifestations of the aura [29]. These findings have been replicated in a recent study [30] in which aura occurred for the first time under experimental hypoxic conditions also in two migraine without aura volunteers. These studies agree in considering hypoxia a powerful trigger of migraine attack with or without aura.…”
Section: Is Ischemia Involved In Migraine?mentioning
confidence: 69%
“…It has been shown that exposure of migraine subjects to normobaric hypoxia can trigger both the migraine attacks and the manifestations of the aura [29]. These findings have been replicated in a recent study [30] in which aura occurred for the first time under experimental hypoxic conditions also in two migraine without aura volunteers. These studies agree in considering hypoxia a powerful trigger of migraine attack with or without aura.…”
Section: Is Ischemia Involved In Migraine?mentioning
confidence: 69%
“…The mechanisms responsible for these metabolic responses are likely numerous, although the release of cyclooxygenase (COX)-derived vasoconstricting prostanoids and other eicosanoid metabolites of arachidonic acid plays a key role ( Fordsmann et al, 2013 , Gariepy et al, 2017 , Shibata et al, 1992 ). Reduced blood flow and tissue oxygenation can trigger a migraine attack in susceptible individuals ( Appenzeller, 1994 , Arngrim et al, 2016 , Broessner et al, 2016 , Frank et al, 2020 , Schoonman et al, 2006 ). These findings, together with the notion that reduced blood flow and tissue oxygenation lead to the sensitization of nociceptors in other tissues ( Hillery et al, 2011 , MacIver and Tanelian, 1992 , Mense and Stahnke, 1983 ), raises the possibility that the mechanisms responsible for driving dural nociceptors in the wake of CSD involve similar vascular and metabolic changes.…”
Section: Cortical Vascular and Metabolic Changes May Not Drive Mening...mentioning
confidence: 99%
“…These include higher prevalence of migraines in elevated regions ( 9 , 10 ) oxidative stress as mechanism for migraine triggers ( 11 ), detection of tissue hypoxia during cortical spreading depression ( 12 ) and, foremost, safe and successful induction of migraine headache in experimental settings utilizing hypoxia ( 13 ). The hypoxic challenge performed in this study has been described in an earlier publication of our group ( 14 ).…”
Section: Introductionmentioning
confidence: 99%